A histopathological evaluation of ovarian hyperstimulation syndrome on reproductive and vital organs and the role of the VEGF-PKA pathway in a mouse model - Karabulut, Seda; Korkmaz, Oya; Erdem Altun, Ceren; Keskin, İlknur (Karger, 2021)
Ovarian hyperstimulation syndrome (OHSS) is one of the most common and iatrogenic complications of in vitro fertilization therapy, which is an exaggerated response to excess hormones resulting in the development of a large number of maturing follicles. Although the complications of and reasons for the condition are well known, the overall histopathological effects on systemic organs and the extent of the damage have not been fully elucidated. Besides, the mechanism that underlies the situation is not very well known. The aim of the present work was to analyse the histopathological effects of OHSS on reproductive (uterus and ovary) and vital organs (liver and kidney) and the possible role of the VEGF-PKA pathway in triggering the condition. Balb/c mice were used to establish an OHSS model. The OHSS group were injected with overdose PMSG while the normal responder group were injected with an optimal dose. Histopathological evaluation was utilised in the liver, kidney, ovary, and uterus stained with hematoxylin and eosin, Masson's trichrome, and periodic acid-Schiff stain. The expression profiles of VEGF (vascular endothelial growth factor), PKA (protein kinase A), and p-PKA (an activated form of PKA) were detected with immunohistochemistry and Western blotting. OHSS was demonstrated to have a negative histopathological effect on all of the organs analysed. These effects were associated with an overall increase in the expression levels of VEGF, PKA, and p-PKA. OHSS has a serious histopathological negative effect on the systemic and reproductive organs and is proven to affect overall health, and thus should be considered a dangerous complication during ART techniques. The activation of the VEGF-PKA pathway, which is indicated by the expression levels of VEGF, PKA, and p-PKA, is demonstrated to accompany this complication, which should be further elucidated to understand the mechanisms underlying the condition.
Keywords: Histopathology; Ovarian Hyperstimulation Syndrome; Protein Kinase A; Vascular Endothelial Growth Factor